2019
DOI: 10.1523/jneurosci.1357-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Coupling under Chronic Stress Is Modified by Altered GABAergic Interneuron Activity

Abstract: Neurovascular coupling (NVC), the interaction between neural activity and vascular response, ensures normal brain function by maintaining brain homeostasis. We previously reported altered cerebrovascular responses during functional hyperemia in chronically stressed animals. However, the underlying neuronal-level changes associated with those hemodynamic changes remained unclear. Here, using in vivo and ex vivo experiments, we investigate the neuronal origins of altered NVC dynamics under chronic stress conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…There is a decline in the number of interneurons, particularly nNOS-expressing interneurons, with aging ( Miettinen et al, 1993 ; Necchi et al, 2002 ), and the removal of their tonic vasodilatory signal could contribute to decreases in cerebral blood flow that are thought to lead to dementia ( Wolters et al, 2017 ). Indeed, alterations of nNOS expression have been implicated in Alzheimer’s disease ( Han et al, 2019b ) and chronic stress ( Han et al, 2019a ). Protecting these neurons from insults and damage could be a promising strategy for preventing neurovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a decline in the number of interneurons, particularly nNOS-expressing interneurons, with aging ( Miettinen et al, 1993 ; Necchi et al, 2002 ), and the removal of their tonic vasodilatory signal could contribute to decreases in cerebral blood flow that are thought to lead to dementia ( Wolters et al, 2017 ). Indeed, alterations of nNOS expression have been implicated in Alzheimer’s disease ( Han et al, 2019b ) and chronic stress ( Han et al, 2019a ). Protecting these neurons from insults and damage could be a promising strategy for preventing neurovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple signaling pathways and molecules implicated in linking neural activity (both directly and indirectly) to arteriole dilations ( Attwell et al, 2010 ; Cauli and Hamel, 2010 ; Kleinfeld et al, 2011 ; Lacroix et al, 2015 ; Longden et al, 2017 ). While no single mechanism likely underlies neurovascular coupling, there is an extensive literature connecting the vasodilator nitric oxide (NO) to vasodilation both in the periphery and the brain ( Tanaka et al, 1991 ; Iadecola, 1992 ; Adachi et al, 1994 ; Stefanovic et al, 2007 ; Hosford and Gourine, 2019 ; Han et al, 2019a ). Recent in vitro evidence indicates neuronally-generated nitric oxide acts directly on arteries, while astrocytic signals control capillary dilations ( Mishra et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, disturbances in blood flow and the processes that regulate it are increasingly appreciated to play a key role in a variety of pathological conditions. These include dementias such as Alzheimer's disease (AD) (Alsop et al, 2000;Iadecola, 2004;Nicolakakis and Hamel, 2011;Iturria-Medina et al, 2016), small vessel disease of the brain (Dabertrand et al, 2015;Capone et al, 2016;Huneau et al, 2018), psychological conditions such as schizophrenia (Mathew et al, 1988;Zhu et al, 2017) and chronic stress (Longden et al, 2014;Han et al, 2019), plus diabetes (Mogi and Horiuchi, 2011;Vetri et al, 2012), hypertension (Girouard and Iadecola, 2006;Capone et al, 2012), and stroke (Girouard and Iadecola, 2006;Koide et al, 2012;Balbi et al, 2017), and pericytes appear to be exceptionally sensitive to pathological perturbations (Winkler et al, 2011).…”
Section: Control Of Pericyte V M By Pericyte Ion Channels and Gpcrs-cmentioning
confidence: 99%
“…While this simple interpretation, that positive and negative BOLD signals reflect increases and decreases in net activity, lends itself easily to investigations of cognitive function in humans, it may not always hold true. Pharmacological studies blocking both glutamate and -aminobutyric acid (GABA) receptors have shown that both neurotransmitters are likely involved in neurovascular coupling [30,38,39]), suggesting that haemodynamic responses (and, therefore, the BOLD signal) are elicited by a combination of signals from excitatory and inhibitory neurons. Indeed, inhibitory interneurons may play a more important role in the production of BOLD signals than was previously appreciated.…”
Section: Part 1: Neurovascular Couplingmentioning
confidence: 99%